Ideias napoleônicas e o grande inquisidor: sobre a militância comunista de Anna Seghers e Jorge Amado - Eggensperger, Klaus (Contingentia, 2009)
The lifelong friendship between Anna Seghers and Jorge Amado began in the late 1940s, when both were engaged in the international comunist struggle for world peace. After becoming disillusioned with the stalinist tyranny, Amado left the PC, whereas Seghers officially continued to follow the party line. She concealed her critique of (post-) stalinist theory and practice in some essays on literature history, especially on Tolstoy, Dostoevsky and Schiller – essays which she dedicated to Amado, who would understand the problems and contradictions within her political involvement.